2009
DOI: 10.1088/0957-0233/20/7/074001
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Δtstrategy for particle image velocimetry (PIV) error correction, applied to a hot propulsive jet

Abstract: PIV (particle image velocimetry) is a measurement technique with growing application to the study of complex flows with relevance to industry. This work is focused on the assessment of some significant PIV measurement errors. In particular, procedures are proposed for estimating, and sometimes correcting, errors coming from the sensor geometry and performance, namely peak-locking and contemporary CCD camera read-out errors. Although the procedures are of general application to PIV, they are applied to a partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 15 publications
4
29
0
Order By: Relevance
“…The technique assumes a second-order polynomial displacement in time, whose coefficients are calculated by maximizing the matching of correlation functions computed at different time. Nogueira et al (2009Nogueira et al ( , 2010) introduced a multiple Dt strategy for the quantitative estimate of the magnitude of peak-locking and CCD read-out bias errors. However, because no correction can be obtained for the instantaneous velocity measurement, the method can only be applied to lower the error of the time-averaged velocity field.…”
Section: Introductionmentioning
confidence: 99%
“…The technique assumes a second-order polynomial displacement in time, whose coefficients are calculated by maximizing the matching of correlation functions computed at different time. Nogueira et al (2009Nogueira et al ( , 2010) introduced a multiple Dt strategy for the quantitative estimate of the magnitude of peak-locking and CCD read-out bias errors. However, because no correction can be obtained for the instantaneous velocity measurement, the method can only be applied to lower the error of the time-averaged velocity field.…”
Section: Introductionmentioning
confidence: 99%
“…But the random part of peak-locking error is much less documented, although Willert et al (1998) and Raffel et al (1997) already mentioned it; later Nogueira et al (2011) showed that peak locking do not only bias the measurement ensemble average, but also originate a strong rms component that affects the measurement of velocity fluctuations. In addition, Nogueira et al (2009) reveal another error type, identifying the existence of significant readout errors from contemporary 12-bit CCD cameras, and quantifying it for some PIV applications.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous works (Nogueira et al 2009(Nogueira et al , 2011, the authors took advantage of this property in order to assess these errors separately using a multiple Dt strategy. Instead of the classical procedure involving a constant Dt for a measurement series, the only difference when this technique is applied consists on acquiring two or more subseries, each with a specific Dt.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations